Defection, recruitment and social change in cooking practices: Energy poverty through a social practice lens. (December 2017) - Herington, M.J.; Lant, P.A.; Smart, S.; Greig, C.; van de Fliert, E.
Abstract: Around the world, more than two thirds of the population persist with traditional cooking practices that are deeply embedded within cultural and social norms. This paper discusses insights from a qualitative study on how changes emerge and unfold in these socially embedded energy practices. The research draws on social practice theory to help make sense of the motivations and social processes behind shifting away from a traditional and social norm, and adopt alternative, modern energy practices. Insights are drawn from primary data collected across two study phases in 2015 and 2016 from the Chittoor district of Andhra Pradesh, India. Findings suggest the importance of energy poverty interventions to integrate and consider both intrinsic and extrinsic incentives, practice leadership and positive relations between communities and the institutions that provide support. We conclude by reflecting on the implications of these findings for the design of policies and interventions aiming to inspire a social change amongst the energy impoverished.